Valeria Belvedere 1989 - 1991. - Valeria Belvedere, Milano (Milano : Valeria Belvedere, 1991)
Astore, Salvatore ; Quartana, Luca ; Nagasawa ; Caracciolo, Roberto ; Guerzoni, Franco ; Ferraris, Carlo ; Verone, Giacinto ; Astore, Salvatore ; Karpüseeler ; Wilson, Richard
Overzicht tentoonstellingen van september 1989 tot september 1991
Italiaans & Engels
boek